2016
DOI: 10.1556/066.2016.45.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Western and Mediterranean-type dietary patterns and anxiety and stress

Abstract: In this study we investigated the relationship between dietary patterns and anxiety and stress in adults living in Shiraz, Iran. In a cross-sectional design, 416 subjects (180 men and 236 women) aged 20 to 50 years were selected by stratifi ed multistage random sampling. Dietary intakes were assessed using a semi-quantitative food frequency questionnaire (FFQ). Mental health information was collected by depression, anxiety and stress scale (DASS) questionnaire. Three major dietary patterns were extracted by fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(20 reference statements)
3
2
0
Order By: Relevance
“…In line with our study, Pengpid et al found that vegetable consumption did not signi cantly decrease the risk of major depression and generalized anxiety disorder [37]. Also, these ndings were consistent with a study in Iranian which stated that vegetable consumption was not associated with anxiety and stress [22]. On the other hand, several studies have shown that vegetable consumption has a protective effect against mental disorders [19,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our study, Pengpid et al found that vegetable consumption did not signi cantly decrease the risk of major depression and generalized anxiety disorder [37]. Also, these ndings were consistent with a study in Iranian which stated that vegetable consumption was not associated with anxiety and stress [22]. On the other hand, several studies have shown that vegetable consumption has a protective effect against mental disorders [19,23].…”
Section: Discussionsupporting
confidence: 93%
“…Similar ndings have also been demonstrated in Chinese adolescents [21]. A strong positive association has been found between "Western" dietary pattern and anxiety and stress; also, there was an inverse association between Mediterranean-type dietary pattern and anxiety in Iranian population [22]. The majority of studies have tried to assess the relationship between dietary patterns and depression, this is while a few number of studies have focused on association between dietary patterns and anxiety [23].…”
Section: Introductionsupporting
confidence: 73%
“…In line with our research, Pengpid et al found that vegetable consumption did not significantly decrease the risk of major depression and generalized anxiety disorder [ 50 ]. Also, these findings were consistent with a study in Iranian which stated that vegetable consumption was not associated with anxiety and stress [ 28 ]. On the other hand, several studies have shown that vegetable consumption has a protective effect against mental disorders [ 23 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have also been demonstrated in Chinese adolescents [ 27 ]. In line with these findings, a strong positive association has been found between the western dietary pattern and anxiety and stress; also, there was an inverse association between a Mediterranean-type dietary pattern and anxiety in an Iranian population [ 28 ]. The majority of studies have tried to assess the relationship between dietary patterns and depression, while a few studies have focused on the association between dietary patterns and anxiety [ 29 ].…”
Section: Introductionmentioning
confidence: 64%
“…Besides, no significant association was noted between dietary patterns and anxiety. Similar to this finding, another dataset also failed to show any connection between adherence to a Mediterranean-type diet loaded with salads, tofu, beans, yogurt, red wine, fruits, and nuts, and anxiety in 20–90 years women [ 41 ]. However, some studies counteract our results.…”
Section: Discussionmentioning
confidence: 57%